Reconfiguring Islamic Authority in Indonesia: The Role of Ulama and Digital Media in Religious Practices - Anam Besari; Vicheka Rith; Ravi Dara (Yayasan Adra Karima Hubbi, 2025)
The digital revolution has profoundly reshaped the landscape of religious authority and practice in the Muslim world, challenging traditional clerical hierarchies. In Indonesia, the authority of the ulama, long central to the dissemination of Islamic knowledge, now coexists with a vibrant and often unregulated digital sphere. This study aimed to investigate how digital media is reconfiguring traditional Islamic authority and influencing the religious practices of Indonesian Muslims. The primary objective was to analyze the strategies employed by both traditional ulama and new digital religious figures in this evolving media ecosystem. A qualitative methodology was employed, combining digital ethnography of popular religious social media platforms with in-depth, semi-structured interviews with established ulama and emergent